Design and implementation of scanning electrochemical microscopy (SECM) for scanning open circuit potential system on damaged coated surfaces - Beheshti, M. (Asian Research Publishing Network, 2016)
Scanning Electrochemical Microscopy (SECM) is used for studying the corrosion of metals in fluid environments with high sensitivity. This microscope measures the current in an ultrafine electrode with a radius between a few nanometers to 25 microns when it is in a solution and near the matrix. Scanning of the surface reactions in microscopic scale will be possible by the use of this technique. The scanning electrochemical microscope with sensitivity of 100 Î¼v and 50 Î¼m displacement in longitudinal and latitudinal axes was designed and fabricated in this research. Au and Pt electrodes were used as working and reference electrodes. Producing topographic images of potential variations in area scan is one of the most important outputs of this microscope which images are presented in colorful and 3-dimensional features on the intensity-based potential variations. Some experiments were done by using the fabricated SECM for assessment of corrosion of coated steel. Investigations were carried out on scratched samples. Examination of results of utilizing SECM showed that the potential of scratched surfaces is significantly higher than that in sound surfaces. So it can be deduced that this microscope can detect the initiation of corrosion and nucleation of pits in its initial stages of nucleation in a corrosive solution. Â© 2006-2016 Asian Research Publishing Network (ARPN). All rights reserved.